A comparative study of aging characteristics and thermal stability of oil palm ash, silica, and carbon black filled natural rubber vulcanizates. Issue 6 (24th July 2013) - Ooi, Zhong Xian; Ismail, Hanafi; Bakar, Azhar Abu
ABSTRACT Filler‐filled natural rubber (NR) vulcanizates were prepared by conventional laboratory‐sized two roll mills and cured using sulfuric system. The effect of thermal aging on physical properties and thermogravimetric analysis (TGA) of oil palm ash (OPA) and commercial fillers (i.e., silica vulkasil C and carbon black N330)‐filled NR vulcanizates at respective optimum loading and equal loading were studied. Before aging, the OPA‐filled vulcanizates showed comparable optimum strength as carbon black‐filled vulcanizates. The hardening of aged filler‐filled NR vulcanizates happened after aging, thereby tensile strength and elongation at break reduced while the modulus increased. Fifty phr carbon black‐filled vulcanizates showed better retention in tensile properties as compared to silica (10 phr) and OPA (1 phr). This was attributed to the addition of different filler loading and this finding was further explained when equal loading of filler‐filled vulcanizates was studied. Fourier transform infra‐red analysis showed chemical structure had changed and tensile fractured surface exhibited smooth appearance due to the deterioration in tensile properties after aging. TGA also denoted the thermal stability was depending on the amount of filler loading. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 4474–4481, 2013